Review: Theologische Realenzyklopädie. Band 33. Technik—Transzendenz - Morgan, Robert (The journal of theological studies, 2003)
Theologische Realenzyklopädie. Band 33. Technik—Transzendenz Gerhard Müller 810 Berlin and New York Walter de Gruyter 2002 €198 3 11 017132 5